Aplikasi Metode Adams-Bashforth-Moulton Model Verhulst Pada Hasil Panen Padi di Kabupaten Jombang - Lukman Hanafi; Kamiran; Sadjidon; Rizki Eko Prasetyo (Limits: Journal of Mathematics and Its Applications, 2024)
Rice is one of the main crops produced by agricultural commodities which is staple food of most Indonesian people. The availability of rice is needed to anticipate the emergence of problems in the future such as population growth, changes in seasons, or as an export commodity. Estimation of rice availability in the future can be done by forming a mathematical model, where the mathematical model used is the Verhulst logistic model. The differential equations in the Verhulst model are first solved using Runge-Kutta method to obtain four initial solutions to be used in finding approximate values using the Adams-Bashforth-Moulton method. After obtaining an approximate solution, a comparison of the accuracy based on error is carried out. The Verhulst model with a step size and carrying capacity rice harvest at Jombang Regency limited 500,000 tons, 600,000 tons, and 700,000 tons, obtained rate error values from numerical solution of Adams-Bashforth-Moulton method is 3.35%, 3.39%, and 3.36%.